Creating and Validating Educational Material for Patients Undergoing Orthognathic Surgery - Cristina Silva Sousa, MSc; Ruth Natalia Teresa Turrini, PhD (Elsevier, 2012)
Purpose: To create and validate educational material for patients undergoing orthognathic surgery. Methods: The design included five phases: (a) a review of the literature regarding surgical complications; (b) gathering information on the needs of patients through blogs and virtual communities; (c) evaluating patient perceptions of the post-operative period through a focus group; (d) obtaining information through specialists using the Delphi technique and validation by judges; and (e) validation by patients in terms of understanding the exhibited material. Results: The first three phases of the study and the first round of the Delphi technique assisted in generating the perioperative patient booklet. The following rounds of the Delphi technique introduced modifications to improve the material, with the judges agreeing on the final material to be validated by patients. Conclusion: Creating a booklet involves more than simply writing summarized ideas on a paper and handing it to the patient. One must understand the population, involve the relevant professionals, and obtain high-quality graphic aids for this type of educational material.